1998
DOI: 10.1073/pnas.95.14.8398
|View full text |Cite
|
Sign up to set email alerts
|

Local mechanical stimulation induces components of the pathogen defense response in parsley

Abstract: Cell suspension cultures of parsley (Petroselinum crispum) have previously been used as a suitable system for studies of the nonhost resistance response to Phytophthora sojae. In this study, we replaced the penetrating fungus by local mechanical stimulation by using a needle of the same diameter as a fungal hypha, by local application of a structurally defined fungus-derived elicitor, or by a combination of the two stimuli. Similar to the fungal infection hypha, the local mechanical stimulus alone induced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…However, detailed analysis of the structures formed in response to non-biotic, mechanical wounds revealed that they are distinct in their composition and likely in their function from fungus-induced CWAs (Russo and Bushnell, 1989). In addition, no papilla formation was detected in response to mechanical (needle) stimulation of parsley suspension culture cells, despite detection of other responses associated with pathogen recognition such as reactive oxygen intermediates (ROI) production and induction of several elicitor-response genes (Gus-Meyer et al, 1998). Although there is no absolute association between papilla formation and resistance to fungal penetration, delayed formation of CWAs is correlated with enhanced fungal infection (Assaad et al, 2004).…”
Section: The Battleground: Structural and Functional Aspects Of The Fmentioning
confidence: 95%
“…However, detailed analysis of the structures formed in response to non-biotic, mechanical wounds revealed that they are distinct in their composition and likely in their function from fungus-induced CWAs (Russo and Bushnell, 1989). In addition, no papilla formation was detected in response to mechanical (needle) stimulation of parsley suspension culture cells, despite detection of other responses associated with pathogen recognition such as reactive oxygen intermediates (ROI) production and induction of several elicitor-response genes (Gus-Meyer et al, 1998). Although there is no absolute association between papilla formation and resistance to fungal penetration, delayed formation of CWAs is correlated with enhanced fungal infection (Assaad et al, 2004).…”
Section: The Battleground: Structural and Functional Aspects Of The Fmentioning
confidence: 95%
“…Because these experiments involved treatment of plant cells with a single stimulus, the flg22 peptide, it should be interesting to study FLS2 localization underneath surface colony-forming pathogenic Pseudomonas cells. Direct evidence that MAMP treatment alone is insufficient to induce the characteristic cell polarization process seen in bacterial interactions or those with filamentous parasites was demonstrated by co-stimulation experiments of individual plant cells with a MAMP from an oomycete pathogen (Pep-25) and mechanical stimulation using a needle of the same diameter as a fungal hypha [93]. Whereas mechanical stimulation alone induced polarized migration of intracellular organelles and the production of reactive oxygen intermediates (ROS), MAMP treatment induced ROS accumulation and the activation of a subset of defense-related genes [93].…”
Section: Opinionmentioning
confidence: 99%
“…Direct evidence that MAMP treatment alone is insufficient to induce the characteristic cell polarization process seen in bacterial interactions or those with filamentous parasites was demonstrated by co-stimulation experiments of individual plant cells with a MAMP from an oomycete pathogen (Pep-25) and mechanical stimulation using a needle of the same diameter as a fungal hypha [93]. Whereas mechanical stimulation alone induced polarized migration of intracellular organelles and the production of reactive oxygen intermediates (ROS), MAMP treatment induced ROS accumulation and the activation of a subset of defense-related genes [93]. However, co-stimulation triggered most of the early responses seen in interactions on fungal attack but was still insufficient to trigger papilla formation [93].…”
Section: Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical interaction has been experimentally decoupled from chemical signaling by replacing the hypha with a needle mimic. Even a gentle touch with a tungsten needle induces several, though not all, of the reactions observed after elicitor treatment or true infections, including the activation of some defense-related genes and the migration of nucleus and cytoplasm toward the site of physical contact (1).…”
Section: From Elicitor Perception To Secondary Metabolite Accumulationmentioning
confidence: 99%